The research of conditions for increasing the competitiveness of snack products in the food industry - Сохацкая, Анна Владимировна (Technology audit and production reserves, 2016)
Research of formation of competition conditions in the segment of snack products of the food industry is investigated in the article. The structure and dynamics of the consumption of products by product groups are analyzed. The key market trends in the economic downturn are highlighted based on market analysis. Industry leaders are determined by product groups, as well as the nature of competition between them. The analysis of activity conditions of the leading manufacturers reveales the priorities of snack market development, taking into account the impact of the key factors of competitiveness. The analysis found that companies in this segment have a considerable export potential due to the presence of a strong raw material base. The market is unsaturated and is in a growth phase with the prospect of significant expansion. Competition is oligopolistic in nature; the key parameters of competitiveness in the domestic market are price, range and channels to promote products. Among the most important factors in the formation of the competitive environment, which are established in the course of the research, macroeconomic, technological and seasonal factore are highlighted. These results allow to establish priorities for production development of distributions of the products for enterprises of this sector, taking into account the influence of competitiveness factors, the use of the key competitive advantages for development of innovation-technology and marketing potential in the conditions of macroeconomic instability.